Projeto gráfico para o livro de culinária “a grande cozinha online” - Sato, Adrielly Francine (2011)
This work was developed to the conclusion project for Graphic Arts Technology’s course at the Federal Technological University of Paraná, elaborated by the student Adrielly Francine Sato, supervised by the professor Marcos Varassin Arantes. The main purpose of this work was created the graphic design for a cookbook about cake, cookies and desserts targeted toward young female that have basic knowlegdes in culinary. The book has as its content the informations and recipes of 10 personal Brazilian cooking blogs with some visibility in the virtual environment. From the research and review of the main concepts of graphic design, analysis of similar publications and the directives of the briefing, was created a visual solution that explored concepts of memories, affection and nostalgia in a consistent graphic composition. Thus, this work contains the detailed report of all the process steps, including from research and analysis, conceptualization and implementation of graphic design, the production of the photographies and the budget and production specifications.